Fluoride-free strong-acid-free reverse flotation method for extracting high-purity quartz sand flotation product from granite pegmatite

By employing a fluorine-free and strong acid-free reverse flotation method, combined with grading crushing, grinding, and magnetic separation processes, and using a combination of quartz mixed inhibitors, the problem of low separation efficiency of quartz and feldspar in granite pegmatite has been solved. This has enabled the green and efficient extraction of high-purity quartz sand and improved the quality of feldspar products, making it suitable for industrial applications.

CN121016943APending Publication Date: 2025-11-28CENT SOUTH UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511450530.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-11
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing technologies for extracting high-purity quartz sand from granite pegmatite suffer from problems such as equipment corrosion, significant environmental hazards, low efficiency, and poor selectivity due to the use of fluorine and strong acids.

Method used

A fluorine-free and strong acid-free reverse flotation method is adopted. Through the processes of graded crushing, grinding, wet magnetic separation and reverse flotation, a combination of quartz mixed inhibitors (sodium metasilicate, sodium tripolyphosphate, sodium hexametaphosphate, carboxymethyl cellulose and saline water glass, etc.) is used in combination with guar gum, gum arabic, sodium humate and citric acid to achieve selective separation of quartz and feldspar.

Benefits of technology

This method enables efficient and environmentally friendly extraction of high-purity quartz sand from granite pegmatite, avoiding equipment corrosion and environmental pollution. It also improves the silica content in quartz products and the quality of potassium and sodium oxide in feldspar products, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016943A_ABST
    Figure CN121016943A_ABST
Patent Text Reader

Abstract

The invention discloses a fluoride-free strong-acid-free reverse flotation method for extracting a high-purity quartz sand flotation product from granite pegmatite, and belongs to the technical field of mineral flotation. The method comprises the following steps: carrying out graded crushing and ore grinding on granite pegmatite to obtain slurry to be treated; carrying out wet magnetic separation on the to-be-treated slurry to obtain ore pulp after magnetic separation and magnetic-containing minerals; the pH value of the ore pulp is not adjusted, reverse flotation is carried out in the presence of a quartz mixed inhibitor, and a feldspar product and a quartz product are obtained; the quartz mixed inhibitor is a combination of a component A and a component B, wherein the component A is selected from at least one of sodium metasilicate, sodium tripolyphosphate, sodium hexametaphosphate, carboxymethyl cellulose and salinized water glass; the component B is selected from at least one of guar gum, Arabic gum, sodium humate and citric acid. The method is free of fluorine and strong acid, green and efficient, and is a method for preparing high-purity quartz sand from pegmatite with high industrial application feasibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite, belonging to the field of mineral flotation technology. Background Technology

[0002] High-purity quartz sand is a crucial raw material for strategic emerging industries such as photovoltaic glass, semiconductors, and optical fiber manufacturing, and its preparation technology has attracted much attention. Pegmatite-type quartz deposits are abundant and have high quartz crystallinity, making them a primary raw material for producing high-purity quartz sand. However, they are often accompanied by aluminosilicate minerals such as dolomite and mica; therefore, effective purification and impurity removal are essential.

[0003] Quartz and feldspar have similar mineralogical structures, making flotation separation difficult. Currently, traditional flotation processes involving both fluorine and acid, and fluorine-free but acid-free methods, not only cause severe corrosion to equipment and pipelines but also pose significant environmental and health risks. The traditional fluorine-free and strong acid-free method, on the other hand, is inefficient and has poor selectivity. Therefore, developing a green, efficient, and industrially feasible method for preparing high-purity quartz sand from pegmatite is of great significance. Summary of the Invention

[0004] To address the problems existing in the prior art, one of the objectives of this invention is to provide a fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite, and to provide a green, efficient, and industrially feasible method for preparing high-purity quartz sand from pegmatite.

[0005] To achieve the above objectives, a first aspect of the present invention provides a fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite, the method comprising:

[0006] (1) The granite pegmatite is graded, crushed, and ground to obtain the slurry to be processed;

[0007] (2) The slurry to be treated is subjected to wet magnetic separation to obtain magnetically separated slurry and magnetic minerals;

[0008] (3) Without adjusting the pH value of the slurry, reverse flotation is carried out in the presence of quartz mixed inhibitors to obtain feldspar products and quartz products;

[0009] The quartz mixed inhibitor is a combination of component A and component B, wherein component A is selected from at least one of sodium metasilicate, sodium tripolyphosphate, sodium hexametaphosphate, carboxymethyl cellulose and water glass; and component B is selected from at least one of guar gum, gum arabic, sodium humate and citric acid.

[0010] The innovation of this invention lies in the combined inhibitory effect of fluorine-free and strong acid-free inhibitors. Through a crushing-grinding-magnetic flotation method, high-purity quartz sand can be extracted from coarse-grained granite pegmatite without pH adjustment and with minimal negative environmental impact. By using components A and B in combination, the combined inhibitors act synergistically on specific surface sites of the mineral, enhancing both selectivity for quartz and flotation efficiency, unlike single inhibitors which decrease selectivity with increasing dosage.

[0011] As a preferred embodiment, the mass ratio of component A to component B is 1:3 to 5. Excessive component A will negatively impact the flotation of feldspar in quartz reverse flotation; excessive component B will affect costs, while insufficient component B will decrease the recovery rate of quartz products in reverse flotation. A further preferred mass ratio of component A to component B is 1:4 to 5.

[0012] As a more preferred embodiment, the quartz mixing inhibitor is a combination of sodium metasilicate and citric acid, or a combination of sodium tripolyphosphate and guar gum. The inventors have found that, in this preferred embodiment, the silica content in the quartz product can be further increased.

[0013] As a preferred embodiment, the magnetic field strength of the wet magnetic separator is 1.2~1.8T. More preferably, it is 1.3~1.6T.

[0014] As a preferred method, sodium carbonate is added during grinding. The dosage of sodium carbonate is 800~1200 g / t. Sodium carbonate is used to disperse the minerals and improve grinding efficiency.

[0015] As a preferred embodiment, the particle size of the slurry to be treated is -40 mesh to +160 mesh.

[0016] As a preferred embodiment, in step (3), the method further includes, without adjusting the pH value of the slurry, performing roughing on the magnetically separated slurry in the presence of a quartz mixed inhibitor to obtain a coarse quartz product and a coarse feldspar product, then performing multiple scavenging on the coarse quartz product to obtain a quartz product, and then performing fine selection on the coarse feldspar product to obtain a feldspar product.

[0017] The reagents added for both roughing and scavenging are quartz mixed inhibitors, anionic collectors, cationic collectors, and foaming agents.

[0018] As a preferred embodiment, the coarse selection is performed once, and the sweep selection is performed 2 to 5 times.

[0019] As a preferred option, during the roughing process, the amount of quartz mixed inhibitor added is 800~1200g / t, the amount of anionic collector added is 100~500g / t, the amount of cationic collector added is 400~900g / t, and the amount of foaming agent added is 30g / t~80g / t.

[0020] As a better option, during the roughing process, the amount of quartz mixed inhibitor added is 800~1000g / t, the amount of anionic collector added is 100~400g / t, the amount of cationic collector added is 400~800g / t, and the amount of foaming agent added is 40~60g / t.

[0021] As a preferred option, during scavenging, the amount of quartz mixed inhibitor added is 200~900g / t, the amount of anionic collector added is 30~400g / t, the amount of cationic collector added is 50~500g / t, and the amount of foaming agent added is 5~60g / t.

[0022] As a more preferred method, during scavenging, the amount of quartz mixed inhibitor added is 300~800g / t, the amount of anionic collector added is 50~300g / t, the amount of cationic collector added is 100~400g / t, and the amount of foaming agent added is 10~50g / t.

[0023] As a preferred method, the coarse feldspar product is refined twice; the reagent added in the first refinement is component B at 100~400g / t, and the reagent added in the second refinement is component A at 100~600g / t.

[0024] As a better option, during the first fine selection, the amount of component B added is 200~400g / t, and during the second fine selection, the amount of component A added is 200~500g / t.

[0025] It should be noted that the foam product obtained after rough selection is a coarse feldspar product (the coarse feldspar product contains high-quality feldspar, some quartz and mica). In the first fine selection, the coarse quartz product is finely selected, and the high-quality feldspar and quartz products are separated by flotation using inhibitor component B. In the second fine selection, the feldspar is reverse-flotated using inhibitor component A to further separate the mica product that floats up with the feldspar. The product remaining at the bottom of the tank is the feldspar product.

[0026] As a preferred embodiment, the anionic collector is a fatty acid-based collector.

[0027] As a preferred embodiment, the cationic collector is an amine collector.

[0028] As a preferred embodiment, the foaming agent is pine oil and / or octanol.

[0029] As a more preferred embodiment, the anionic collector is selected from at least one of sodium oleate, oleic acid, and talc oil. Sodium oleate is even more preferred.

[0030] As a more preferred embodiment, the amine collector is dodecylamine acetate and / or octadecylamine.

[0031] As a preferred option, the crushing process is divided into three stages: first, the granite pegmatite is initially crushed to a particle size of less than 10 cm, then medium-sized to 3-5 cm, and finally finely crushed to less than 2 cm.

[0032] Compared with the prior art, the present invention has at least the following advantages:

[0033] (1) The process of the present invention is carried out under the conditions of fluorine-free and strong acid-free slurry, which can avoid corrosion of mineral processing equipment and pipelines, and at the same time avoid harm to the environment and human body.

[0034] (2) The present invention adopts a combined process of magnetic separation and flotation, which can effectively remove iron-containing minerals and mica-like minerals, reduce the Fe content in quartz and feldspar products, increase the silica content in quartz products, and improve the quality of potassium and sodium in feldspar products.

[0035] (3) The process of this invention is simple and the product quality is high, providing technical support for large-scale industrial application.

[0036] (4) The silica content in the quartz product obtained by the present invention reaches 99.6%, and the iron oxide content is less than or equal to 0.02%.

[0037] (5) The feldspar obtained by the present invention is a first-grade product, wherein the sum of the mass of potassium oxide and sodium oxide is greater than or equal to 11.50%, and the content of iron oxide is less than or equal to 0.15%. Attached Figure Description

[0038] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0039] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0040] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by those skilled in the art without creative effort are still within the scope of protection of the present invention.

[0041] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0042] Example 1

[0043] In this embodiment, a granite pegmatite from Fujian Province was used as the raw ore. The content of its main substances was determined and is shown in Table 1.

[0044] The reverse flotation method provided in this embodiment specifically includes the following steps:

[0045] (1) Pre-treatment (crushing and grinding): The raw ore is graded and crushed. A jaw crusher is used for coarse crushing to below 10 cm; a cone crusher is used for medium crushing of the coarse crushed product to 3-5 cm; a double roll crusher is used for fine crushing of the medium crushed product to below 2 cm. 500g of the crushed mineral is weighed, and 1000g of sodium carbonate is added per ton of mineral (to disperse the mineral and improve grinding efficiency). The mineral is then ground to obtain a product with a particle size of -40 mesh to +160 mesh.

[0046] (2) Magnetic separation: A high-gradient magnetic separator (magnetic induction intensity of 1.6T) is used to perform magnetic separation on the products;

[0047] (3) Feldspar flotation: The flotation process consists of one roughing, two scavenging, and two cleaning stages. The pH value is not adjusted throughout the process (the natural pH value is 4-5). During roughing, the amount of mixed quartz inhibitor added is 1000 g / t, the amount of anionic collector added is 300 g / t, the amount of cationic collector added is 600 g / t, and the amount of frother added is 50 g / t. For the scavenging of the quartz residue at the bottom of the tank, during the first scavenging, the amount of mixed quartz inhibitor added is 500 g / t, the amount of anionic collector added is 200 g / t, the amount of cationic collector added is 400 g / t, and the amount of frother added is 30 g / t. During the second scavenging, the amount of mixed quartz inhibitor added is 400 g / t, the amount of anionic collector added is 100 g / t, the amount of cationic collector added is 200 g / t, and the amount of frother added is 10 g / t. The foam product obtained from the roughing process is a coarse feldspar product (containing high-quality feldspar, some quartz, and mica), while the residue at the bottom of the tank is a quartz product. Further refining of the coarse feldspar product is then performed. In the first refining, component B is added at 250 g / t, without the addition of anionic / cationic collectors or frothers. A second refining is then performed on the resulting foam product. In the second refining, component A is added at 500 g / t, without the addition of anionic / cationic collectors or frothers, and feldspar reverse flotation is conducted. The residue at the bottom of the tank is ultimately the feldspar product.

[0048] In this embodiment, the anionic collector is sodium oleate; the cationic collector is dodecylamine acetate; the quartz mixed inhibitor is composed of sodium metasilicate (component A) and citric acid (component B) in a mass ratio of 1:4; and the foaming agent is pine oil.

[0049] Example 2

[0050] In this embodiment, a granite pegmatite from Fujian Province was used as the raw ore, similar to Embodiment 1.

[0051] The reverse flotation method provided in this embodiment specifically includes the following steps:

[0052] (1) Pre-treatment (crushing and grinding): The raw ore is graded and crushed. A jaw crusher is used for coarse crushing to below 10 cm; a cone crusher is used for medium crushing of the coarse crushed product to 3-5 cm; a double roll crusher is used for fine crushing of the medium crushed product to below 2 cm. Then, 500g of the crushed mineral is weighed and ground according to the standard of adding 1200g of sodium carbonate per ton of mineral to obtain a product with a particle size of -40 mesh to +160 mesh.

[0053] (2) Magnetic separation: A high-gradient magnetic separator (magnetic induction intensity of 1.3T) is used to perform magnetic separation on the products;

[0054] (3) Feldspar flotation: A flotation process consisting of one roughing, three scavenging, and two cleaning stages is adopted. The pH value is not adjusted throughout the process (the natural pH value is 4-5). During roughing, the amount of quartz mixed inhibitor added is 1000 g / t, the amount of anionic collector added is 400 g / t, the amount of cationic collector added is 800 g / t, and the amount of frother added is 60 g / t. For the quartz residue at the bottom of the tank, scavenging is performed. During the first scavenging, the amount of quartz mixed inhibitor added is 600 g / t, the amount of anionic collector added is 200 g / t, the amount of cationic collector added is 400 g / t, and the amount of frother added is... The initial concentration was 30 g / t; during the second scavenging, the concentration of the mixed quartz inhibitor was 500 g / t, the concentration of the anionic collector was 150 g / t, the concentration of the cationic collector was 300 g / t, and the concentration of the frother was 30 g / t; during the third scavenging, the concentration of the mixed quartz inhibitor was 300 g / t, the concentration of the anionic collector was 75 g / t, the concentration of the cationic collector was 150 g / t, and the concentration of the frother was 10 g / t. The foam product obtained from the roughing was coarse feldspar (which contained high-quality feldspar, some quartz, and mica), and the residue at the bottom of the tank was quartz. Further fine selection of coarse feldspar products: In the first fine selection, the amount of component B added is 400 g / t, without adding anionic / cationic combined collectors and frothers, and the resulting foam product is then finely selected; In the second fine selection, the amount of component A added is 200 g / t, without adding anionic / cationic combined collectors and frothers, and feldspar reverse flotation is performed, with the final residue at the bottom of the tank being the feldspar product.

[0055] In this embodiment, the anionic collector is sodium oleate; the cationic collector is dodecylamine acetate; the quartz mixed inhibitor is sodium tripolyphosphate (component A) and guar gum (component B) in a mass ratio of 1:4; and the foaming agent is pine oil.

[0056] Example 3

[0057] This embodiment is carried out using a method similar to that of Embodiment 1, except that the quartz mixed inhibitor in this embodiment is replaced with sodium metasilicate and citric acid in a mass ratio of 1:5. The amount of quartz mixed inhibitor used in each flotation process in this embodiment is the same as in Embodiment 1.

[0058] Example 4

[0059] This embodiment is carried out using a method similar to that of Embodiment 1, except that the quartz mixed inhibitor in this embodiment is replaced with sodium metasilicate and citric acid in a mass ratio of 1:6. The amount of quartz mixed inhibitor used in each flotation process in this embodiment is the same as in Embodiment 1.

[0060] Comparative Example 1

[0061] Steps (1) and (2) are the same as in Example 1;

[0062] Step (3): The pH value of the pulp is adjusted to 10.5 using sodium carbonate (sodium carbonate is added as a pH adjuster in this flotation process), and the quartz roughing and scavenging flotation process is carried out. During roughing, the inhibitors used are 200g / t soluble starch, 300g / t anionic collector and 50g / t cationic collector, and the inhibitors used during scavenging are 100g / t soluble starch, 200g / t anionic collector and 40g / t cationic collector.

[0063] The anionic collectors were all sodium oleate; the cationic collectors were all dodecylamine acetate.

[0064] Comparative Example 2

[0065] This comparative example was conducted using a method similar to that of Example 3, except that the quartz mixed inhibitors in this comparative example were all replaced with single citric acid. The amount of citric acid used in the roughing and scavenging processes of this comparative example was the same as that used in each roughing and scavenging process of Example 3, and the fine selection process was the same as that of Example 1.

[0066] Comparative Example 3

[0067] This comparative example was conducted using a method similar to that of Example 3, except that the quartz mixed inhibitors in this comparative example were all replaced with single citric acid. The amount of citric acid used in the roughing and scavenging processes of this comparative example was consistent with the amount of quartz mixed inhibitors (sodium metasilicate and citric acid) used in each flotation process of Example 3. The fine selection process was the same as that of Example 1.

[0068] Test case

[0069] The various indicators of quartz products, feldspar products and raw ore were tested, and the results are shown in Table 1.

[0070]

[0071] As can be seen from Table 1, Comparative Example 1 shows that the quality of quartz cannot be guaranteed after flotation under alkaline conditions. A large amount of aluminosilicate minerals are included in the product, and the quality of feldspar is significantly reduced due to the poor quartz separation effect.

[0072] Comparative Examples 2 and 3 show that when citric acid is used alone as an inhibitor, it is almost impossible to suppress the flotation of quartz, which affects the quality of both quartz and feldspar products and results in poor separation of the two minerals.

[0073] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite, characterized in that: The method includes: (1) The granite pegmatite is graded, crushed, and ground to obtain the slurry to be processed; (2) The slurry to be treated is subjected to wet magnetic separation to obtain magnetically separated slurry and magnetic minerals; (3) Without adjusting the pH value of the slurry, reverse flotation is carried out in the presence of quartz mixed inhibitors to obtain feldspar products and quartz products; The quartz mixed inhibitor is a combination of component A and component B, wherein component A is selected from at least one of sodium metasilicate, sodium tripolyphosphate, sodium hexametaphosphate, carboxymethyl cellulose and water glass; and component B is selected from at least one of guar gum, gum arabic, sodium humate and citric acid.

2. The fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 1, characterized in that: The mass ratio of component A to component B is 1:3~5.

3. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 1 or 2, characterized in that: The particle size of the slurry to be treated is -40 mesh to +160 mesh.

4. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 1 or 2, characterized in that: The magnetic field strength of the wet magnetic separator is 1.2~1.8T.

5. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 1 or 2, characterized in that: In step (3), the method further includes, without adjusting the pH value of the slurry, performing roughing on the magnetically separated slurry in the presence of quartz mixed inhibitors to obtain coarse quartz products and coarse feldspar products, then performing multiple scavenging on the coarse quartz products to obtain quartz products, and then performing fine selection on the coarse feldspar products to obtain feldspar products. The reagents added for both roughing and scavenging are quartz mixed inhibitors, anionic collectors, cationic collectors, and foaming agents.

6. The fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 5, characterized in that: During the roughing process, the amount of quartz mixed inhibitor added is 800~1200g / t, the amount of anionic collector added is 100~500g / t, the amount of cationic collector added is 400~900g / t, and the amount of foaming agent added is 30g / t~80g / t. And / or, during scavenging, the amount of quartz mixed inhibitor added is 200~900g / t, the amount of anionic collector added is 30~400g / t, the amount of cationic collector added is 50~500g / t, and the amount of foaming agent added is 5~60g / t.

7. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 5 or 6, characterized in that: The anionic collector is a fatty acid-based collector; And / or, the cationic collector is an amine collector; And / or, the foaming agent is pine oil and / or octanol.

8. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 7, characterized in that: The anionic collector is selected from at least one of sodium oleate, oleic acid, and talc oil; And / or, the amine collector is dodecylamine acetate and / or octadecylamine.

9. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 5, characterized in that: The coarse feldspar product is subjected to two fine-tuning processes; the first fine-tuning process involves adding 100~400g / t of component B, and the second fine-tuning process involves adding 100~600g / t of component A.

10. A fluorine-free and strong acid-free reverse flotation method for extracting high-purity quartz sand flotation products from granite pegmatite according to claim 1 or 2, characterized in that: The crushing process is divided into three stages: first, the granite pegmatite is initially crushed to a particle size of less than 10 cm; then, it is medium-crushed to 3-5 cm; and finally, it is finely crushed to less than 2 cm.

Citation Information

Cited By

  • Quartz flotation collecting agent, preparation method thereof and flotation method for obtaining different grades of quartz through cascade flotation

    CN121423132A